1) ' +

 

                                           ( + 1)

        1 + 2 + 3 + ... + =

                                                2

" "

1 = 1 2 = 2 .... =

= 1 1

= 2   3

= 3 6

  = 4

:

1) = 1

2) = = + 1

= 1

= 1 ( = 1 )

= 1(1+1)/2 = 2/2 = 1

= 1   (1)    ........ (1)

  = :

                                           ( + 1)

        1 + 2 + 3 + ... + =    ........... (2)   

                                                2

:

 

                                                         ( + 1)[( + 1) + 1]

        1 + 2 + 3 + ... + + ( + 1) =     + 1 (2)

                                                                      2

 

+ 1 +1 + 1

 

+1   .... (2) +1 = + 1

 

                                                          ( + 1)

        1 + 2 + 3 + ... +   + ( + 1)=  + ( + 1)   

                                                                2

 

                                                          ( + 1)         2( + 1)    

                                                     =  +   2 2

                                                                2                  2

 

                                                          ( + 1) + 2( + 1)    

                                                     =       ( + 1)

                                                                        2      

 

                                                         ( + 1)[ + 2]

                                                     =                + 2 = ( + 1) + 1

                                                                   2 

    

                                                         ( + 1)[( + 1) + 1]

                                                     =   +1 (2)

                                                                        2      

 

= + 1    ( + 1)     ......... (3)

 

(1)   (2) (3)